Local reference dose evaluation in conventional radiography examinations in Iran - Shandiz, M. Shirin (J Appl Clin Med Phys, 2014)
The goal of this study was to establish local diagnostic reference levels (LDRLs) for conventional radiography examinations in Sistan‐Baluchestan province of Iran, using dose area product (DAP) measurements followed by a comparison with international dose levels. DAP factor evaluation was carried out at eight radiography rooms in six public and one private health‐care centers. The study employed DAP, exposure, and demographic data (weight, age, height) for 1069 patients who presented for one of the 11 routine radiography examinations: chest (AP, PA, LAT), abdomen (AP), lumbar spine (AP, LAT), pelvis (AP), skull (AP/PA, LAT), and cervical spine (AP, LAT). The data were analyzed statistically and the minimum, median, mean, maximum, and third quartile DAP values were calculated. It was observed that LDRLs for chest PA (0.26 Gy.cm(2)) and chest LAT (0.66 Gy.cm(2)) projections were up to 136% and 113% higher, respectively, than their corresponding NRPB 2005 values. Other radiographic procedures had lower recommended reference doses compared with recently recommended national reference doses published in recent NRPB reports and other studies. Wide variations in DAP values and exposure parameters were observed for similar radiographic procedures between patients in different rooms and for different patients in the same room. These and other observations, such as poor radiographic techniques, high rate of radiographic reject/repeat, and lack of modern X‐ray machines and equipment, show that the need to carry out quality assurance programs is critical in Iran. PACS numbers: 87.53.Bn, 87.59.B